Reviews of recent publications (Studies in 20th & 21st Century Literature, 2004)
Bohn, Willard. The Rise of Surrealism: Cubism, Dada, and the Pursuit of the Marvelous Reviewed by Elena Cueto As Folkart, Jessica A. Angles on Otherness in Post-Franco Spain: The Fiction of Cristina Fernández Cubas Reviewed by Jorge Marí Marí, Jorge. Lecturas espectaculares: El cine en la novela española desde 1970 Reviewed by Salvador A. Oropesa Meredith, James H. Understanding the Literature of World War II: A Student Casebook to Issues, Sources, and Historical Documents Reviewed by Cornelius Partsch Moran, Michael G. and Michelle Ballif, eds. Twentieth-Century Rhetorics and Rhetoricians: Critical Studies and Sources Reviewed by David Malcolm
Keywords: Willard Bohn; The Rise of Surrealism: Cubism Dada and the Pursuit of the Marvelous; Elena Cueto As; Jessica A. Folkart; Angles on Otherness in Post-Franco Spain: The Fiction of Cristina Fernández Cubas; Jorge Marí; Lecturas espectaculares: El cine en la novela española desde 1970; Salvador A. Oropesa; James H. Meredith; Understanding the Literature of World War II: A Student Casebook to Issues Sources and Historical Documents. Cornelius Partsch; Michael G. Moran; Michelle Ballif; Twentieth-Century Rhetorics and Rhetoricians: Critical Studies and Sources; David Malcolm